Sensor Chemical Oxygen Demand (COD) Berbasis TiO2/Ti Sebagai Elektroda Kerja Untuk Mendeteksi Rhodamine B - Syahrir Syahrir; Muh. Nurdin; La Ode Ahmad Nur Ramadhan (University of Halu Oleo, 2020)
Photoelectrocatalytic degradation towards rhodamine B (RhB) organic compound has been conducted by using TiO2/Ti as the working electrode. The preparation of TiO2/Ti working electrode was conducted by using anodizing method to compare the data related to the activity of the electrodes. The results showed that TiO2/Ti electrodes was able to change the surface morphology of the electrodes to become more homogeneous. From the test results photoelectrocatalysis activity was obtained at a COD value of 20.40 mL/L which occurred in RhB dyes with an initial concentration of 10 mg/L. Keywords: photoelectrocatalysis, degradation, rhodamine B, TiO2/Ti. ABSTRAK Degradasi secara fotoelektrokatalitik senyawa organik rhodamine B (RhB) telah dilakukan dengan menggunakan TiO2/Ti sebagai elektroda kerja. Penyusunan elektroda kerja TiO2/Ti disiapkan dengan menggunakan metode anodasi untuk membandingkan data yang berkaitan dengan aktivitas elektroda. Hasil penelitian menunjukkan bahwa elektroda TiO2/Ti mampu mengubah morfologii permukaan elektroda menjadi lebih homogen. Dari hasil uji aktifitas fotoelektrokatalisis diperoleh pada nilai COD 20,40 mL/L yang terjadi pada zat warna RhB dengan konsentrasi awal 10 mg/LKata Kunci: fotoelektrokatalisis, degradasi, rhodamin B, TiO2/Ti.